2020
DOI: 10.3390/jrfm13050097
|View full text |Cite
|
Sign up to set email alerts
|

Innovation and Firm Performance: The Moderating and Mediating Roles of Firm Size and Small and Medium Enterprise Finance

Abstract: This study examines the moderating effect of firm size on the relationship between innovation and firm performance of small and medium enterprises in 29 countries in Eastern European and Central Asia. The study also investigates whether the impact of innovation in products and processes on firm performance is affected by financial capital. The method applied is partial least square structural equation modelling. The findings indicate that firm size and the financial capital both moderate and mediate the impact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(61 citation statements)
references
References 76 publications
1
38
0
Order By: Relevance
“…As a consequence, the main determinants of innovation in SMEs are proposed to be: sector belonging, the particular nature of innovation and the characteristics of the firm itself, such as size and age (Avermaete et al 2003;Bhattacharya and Bloch 2004;Ortega-Argilés et al 2009). Another stream of studies examined the effects of innovation on firm performance (Anwar 2018;Kijkasiwat and Phuensane 2020;Wolff and Pett 2006). Most of the works focus on innovative activity in particular countries (e.g., Hall et al 2009;Lecerf and Omrani 2019 in Germany;Oke et al 2007 in the UK; Varis and Littunen 2010 in Finland).…”
Section: Smes and Innovationsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence, the main determinants of innovation in SMEs are proposed to be: sector belonging, the particular nature of innovation and the characteristics of the firm itself, such as size and age (Avermaete et al 2003;Bhattacharya and Bloch 2004;Ortega-Argilés et al 2009). Another stream of studies examined the effects of innovation on firm performance (Anwar 2018;Kijkasiwat and Phuensane 2020;Wolff and Pett 2006). Most of the works focus on innovative activity in particular countries (e.g., Hall et al 2009;Lecerf and Omrani 2019 in Germany;Oke et al 2007 in the UK; Varis and Littunen 2010 in Finland).…”
Section: Smes and Innovationsmentioning
confidence: 99%
“…However, the existing body of the literature in this field remains focused on the public support for innovative SMEs, as it has been confirmed that firms may face difficulties in finding external market-based finance for intangible (knowledge-based) assets (Lee et al 2015;Vasilescu 2014). Numerous studies have also examined the relevance of venture capital funding and recently-crowdfunding, in the context of innovative SMEs (Anwar 2018;Baldock and Mason 2015;Kijkasiwat and Phuensane 2020;Schenk 2015). The relevance of debt finance and internal funding (determined by the efficient performance) in enhancing innovation in SMEs remains relatively less explored (Kerr and Nanda 2015;Sau 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Also, Canepa and Stoneman (2008), Czarnitzki (2006), and Freel (2007) suggest that all these structural problems with innovative financing firms are amplified in the case of SMEs. Finally, as Kijkasiwat and Phuensane (2020) documented, bigger companies are more able to benefit from external and internal innovative projects, while the smaller ones only benefit from internal projects.…”
Section: Sizementioning
confidence: 88%
“…The benefits of firms undertaking innovation activity are invaluable. Firstly, they positively affect not only the financial results of the company itself but also production processes, productivity, efficiency, productivity, work quality, and organisation [56][57][58]. Secondly, they also affect development and competitiveness in the national and global economy [59][60][61].…”
Section: Business Innovation and Innovation Activity: Theoretical Backgroundmentioning
confidence: 99%